Analysis of Interest In Using Electrical Bicycles in Palangka Raya - Vivien Nopella Valentina; Robby Robby; Sutan Parasian Silitonga (Sainteks: Jurnal Sain dan Teknik, 2023)
Every year the number of population growth is increasing, therefore the use of transportation is also increasing. With the existence of environmentally friendly transportation products, it is hoped that more and more people will contribute to using them to reduce the impact of global warming. One of the environmentally friendly transportation products is an electric bicycle. This study specifically aims to analyze the characteristics of electric bicycle mode selection and analyze the electric bicycle mode selection model in the city of Palangka Raya. The development of electric bicycles in anticipation of depleting reserves of fuel oil has begun. Palangka Raya City is one of the cities where the use of electric bicycles is gaining popularity. The Logit Binomial model was used to analyze the data from the sort of survey employed in this research, which was based on respondents' expressed preferences. According to the findings of the research, it was shown that what influenced interest in choosing the mode of electric bicycle use were the variables age (X1), gender (X2), family structure (X3), motorcycle ownership (X11), long distance traveled (X15), education/school (X22), spending per month (X24) it is obtained that the overall model prediction rate variable is 79%.